(untitled) (Medical Forum Monthly, 2022)
Objective: To assess the pregnancy outcomes among women with uterine fibroids. Study Design: A prospective observational study Place and Duration of Study: This study was conducted at the Gynecology & Radiology department of Bahawal Victoria Hospital Bahawalpur from May 2020 to May 2021 for a period of one year. Materials and Methods: The study included pregnant women with uterine fibroids. Each woman underwent a detailed clinical examination and routine laboratory testing at each antenatal visit. Moreover, fetal health was also assessed regularly through ultrasonography. Parameters including maternal age, size and number of fibroids, obstetric complications, parity, and delivery mode were observed. Results: A total of 60 pregnant women with uterine fibroids were included in the study. The participants had a mean age of 31.56±4.3 years. Primigravida was reported in 25.03% of women while multigravida in 74.97%. 75% of women had spontaneous conception and 25% utilized different treatments for conception. Only 23.2% of women delivered through normal route and C-section was performed in 76.98% of women. 8% of women had a miscarriage, 12% had a postpartum hemorrhage, and only 3% had placenta previa associated antepartum bleeding. 15.4% had premature delivery while 75.2% completed the normal gestation period. Multiple fibroids and intramural location posed a high risk of C-section than single fibroids or sub-serosal fibroids. Conclusion: Uterine fibroids can cause severe pregnancy outcomes. Therefore, it is advised to evaluate the complications regularly during the antenatal period and manage them effectively to avoid adverse obstetric outcomes